Challenges of Investigating Community Outbreaks of Cyclosporiasis, British Columbia, Canada - Shah, Lena (Centers for Disease Control and Prevention, 2009)
Investigations of community outbreaks of cyclosporiasis are challenged by case-patients’ poor recall of exposure resulting from lags in detection and the stealthy nature of food vehicles. We combined multiple techniques, including early consultation with food regulators, traceback of suspected items, and grocery store loyalty card records, to identify a single vehicle for a cyclosporiasis outbreak in British Columbia, Canada, in 2007.